2017
DOI: 10.21511/bbs.12(1-1).2017.02
|View full text |Cite
|
Sign up to set email alerts
|

Testing for explosive bubbles in the South African-US exchange rate using the sequential ADF procedures

Abstract: This paper tests for the existence of speculative bubbles in the South African-US exchange rate using the sequential ADF procedures. In particular, the paper uses the SADF and GSADF right-tailed unit root tests to explore the existence of explosive bubbles in the South African-US exchange rate for the time period running from January1980 through July 2012. The results provide evidence in support of the existence of explosive bubbles in the nominal rand-dollar exchange rate, the real exchange rate of traded and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
1
1
0
1
Order By: Relevance
“…The authors present evidence of two bubbles; the first bubble emerged during [2005][2006] and the second one appeared during the global financial crisis. The same results were obtained by Elike and Anoruo (2017), who provide significant evidence of explosive bubbles in the nominal USDZAR rate, the real exchange rate of traded and non-traded goods. Korkmaz et al (2016) revealed significant evidence in favor of the bubble existence in stock index returns of Bist100, gold, and USDTRY foreign exchange rates, whereas the result was insignificant for the deposit interest rates and EURTRY exchange rates in Turkey.…”
Section: Introductionsupporting
confidence: 82%
See 1 more Smart Citation
“…The authors present evidence of two bubbles; the first bubble emerged during [2005][2006] and the second one appeared during the global financial crisis. The same results were obtained by Elike and Anoruo (2017), who provide significant evidence of explosive bubbles in the nominal USDZAR rate, the real exchange rate of traded and non-traded goods. Korkmaz et al (2016) revealed significant evidence in favor of the bubble existence in stock index returns of Bist100, gold, and USDTRY foreign exchange rates, whereas the result was insignificant for the deposit interest rates and EURTRY exchange rates in Turkey.…”
Section: Introductionsupporting
confidence: 82%
“…The results have significant implications for policymakers in attaining price and financial stability and investors for risk and portfolio management as well as arbitrage opportunities, as the existence of a bubble in a market could create disruptive effects on an economy through redistribution of wealth (Jahan-Parvar and Waters, 2010; Elike and Anoruo, 2017). Given that GSADF tests could be used as a real-time bubble detector (Homm and Breitung, 2012), implementation of this approach and the time-varying causality tests by policymakers could provide important benefits in terms of assessing and measuring risks driven by exogenous or/and endogenous shocks, and taking preemptive measures in the markets.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Birden çok yineleme ile hesaplanan sağ kuyruk ADF testlerinde her alt örneklem ilk gözlem değeri ile başlarken son gözlem değerinin değişmesine izin verilir. Temsili örnek pencere ile gösterilmekte ve küçük örneklemden tüm örnekleme kadar test edilmesine imkân sağlanmaktadır (Elike ve Anoruo, 2017).…”
unclassified